MODERN METHODS OF PROPHYLAXIS AND TREATMENT OF PATHOLOGICAL SCARS OF FACE AND NECK - Avetikov, D.S. (World of Medicine and Biology, 2012)
Work is sanctified to the ground of application of cream of "Dermofibrase" in complex therapy of pathological scars of person and neck. It is well-proven authors, that application of preparation is the high-efficiency and nosotropic reasonable method of treatment. The best result is observed in the first half-year after a trauma, in the period of intensive height of cicatrical tissue.
Keywords: pathological scar; hypertrophic scar; cream of "Dermofibrase"